A passive stress-strain model for concrete prisms reinforced by a combination of confinement reinforcement. (1st November 2021) - Hao, Xin-Kai; Feng, Qian; Zheng, Jian-Jun
Highlights: A passive stress–strain model is presented for concrete prisms reinforced with a combination of confinement reinforcement. The size effect is considered in the proposed approach. The approach can be applied in the ductility design of FRP wrapped concrete prisms. Abstract: The strength and ductility of concrete prisms can be significantly enhanced by confinement reinforcement, such as stirrups, wraps, and tubes. Recently, a combination of confinement reinforcement is applied to concrete prisms for their better ductility or a specific use. However, most existing approaches only give the ultimate strength of confined concrete prisms and do not consider the size effect. As a result, these approaches cannot provide structural engineers with a simple tool for the ductility design of concrete prisms with size effect. In this paper, based on the fundamental partial interaction bond-slip and shear-friction mechanisms, a passive stress–strain model of concrete confined by a combination of confinement reinforcement is proposed. The main advantages of the proposed model are that the size effect is considered and it can be applied to concrete members of rectangular or circular cross-section reinforced by novel combinations of confinement reinforcement. After the proposed model is verified with test results of concrete prisms reinforced by FRP wrapping and stirrups/steel tube, it is concluded that this model can be applied in the ductility design of FRP wrapped concrete prisms.